People's attitudes to autonomous vehicles. (March 2019) - Hudson, John; Orviska, Marta; Hunady, Jan
Highlights: Attitudes to AVs are determined by both self-interest and robot technophobia. People are less hostile to driverless trucks than driverless cars. 45% (8.6%) are totally uncomfortable (comfortable) with driverless cars. The young, men, the well educated and urban dwellers are most in favour of AVs. Abstract: We analyse people's attitudes to autonomous vehicles (AVs), i.e. driverless cars and trucks, using Eurobarometer data relating to November/December 2014 on approximately 1000 people in each EU country. People tend to be lukewarm to AVs, particularly driverless cars. However, a simple average hides the fact that many people, young and old, are totally hostile to the concept and a smaller number totally in favour. AVs are part of a technological development linked in general to robots, and regression analysis finds attitudes tend to be linked to both general attitudes to robots and individual self-interest relating specifically to AVs. Consistent with the literature, we find the young to be more in favour than the elderly. There are other differences, with males, those in cities and the more educated being more in favour, as well as differences between countries. There is also some evidence that support for AVs is greater in countries with high accident rates.